Structural state governs the mechanism of shear-band propagation in metallic glasses - Jinhua Yu; Zhen Zhang; Zhendong Sha; Jun Ding; A. Lindsay Greer; Evan Ma (Proceedings of the National Academy of Sciences, 2025)
Shear bands (SBs) play a critical role in determining the mechanical behavior of metallic glasses (MGs). However, the rapid dynamics and highly localized nature of SB propagation present significant challenges for direct observation of their atomistic mechanisms using experimental techniques. In this study, we employ hybrid molecular dynamics/Monte Carlo simulations to investigate the atomic-scale mechanisms of SB propagation in Mg 65 Cu 25 Y 10 MGs, prepared using cooling rates as slow as 10 4 K s −1 —comparable to experimental casting conditions and significantly slower than the 10 10 K s −1 rates previously employed in atomistic simulations. Our results reveal a qualitative shift in SB propagation mechanisms as the structural state evolves with decreasing cooling rates. In hyperquenched MGs, SB propagation occurs intermittently, characterized by a “stop-and-go” motion driven by sequential activation and coalescence of multiple shear transformation zones (STZs) separated by vortex-like fields. In contrast, slowly cooled MGs exhibit continuous and rapid SB propagation, mediated by localized shear softening and the formation of large vortex fields, indicative of a more collective structural response. This transition arises from significant differences in the number density and spatial distribution of activated STZs across different structural states. These findings provide insights into the microscopic dynamics of SB initiation and propagation in MGs, highlighting how the structural state can be strategically tuned to control SB behavior. This opens up different opportunities for optimizing the mechanical performance of MGs for targeted engineering applications.